Gadolinium retention in the body: what we know and what we can do - Tedeschi, Enrico; Caranci, Ferdinando; Giordano, Flavio; Angelini, Valentina; Cocozza, Sirio; Brunetti, Arturo (Radiologia medica, 2017)
Gadolinium-based contrast agents (GBCA), widely used in Magnetic Resonance Imaging (MRI) for almost 30 years, were recently shown to be deposited in the brain and to induce persistent T1 shortening in deep gray matter structures in subjects with normal renal function. The aim of the present study is to summarize the evidence derived from the rapidly growing scientific literature on Gadolinium retention in the brain and in the rest of the body. To this end, the original articles that described imaging and pathology findings in humans and animals exposed to GBCA were reviewed. The main aspects that emerged were the different effects of linear and macrocyclic GBCA on brain MRI appearance, the evidence of Gadolinium tissue retention in multiple organs, and the debated issue of the possible clinical consequences. Although no adverse health effects have been documented so far, updated information about GBCA build-up in the body is necessary for health professionals, also in view of the increasing concern in the general population. To date, our knowledge about the mechanisms of Gadolinium tissue deposition and, above all, its long-term consequences is still largely incomplete. However, while official guidelines are eagerly awaited, some advices may already be given, to help our radiological daily practice.